HASHIMOTO THYROIDITIS IN 7-YEAR-OLD CHILDREN: A CASE REPORT - Sunardi, Wenny; Dateng Beyeng, Rosalia Theodosia; Parama Siwi, Putu Ianta (JOURNAL OF WIDYA MEDIKA JUNIOR, 2024)
Hashimoto thyroiditis (AIT) is a common cause of hypothyroidism that can occur in childhood and adolescence (ages six to sixteen years) and often occurs in women. AIT can be determined by increases in TSH with normal thyroid hormone serum levels. The diagnosis of AIT based on clinical symptoms of hypothyroid, biochemical results, and ultrasound images. Treatment is carried out by administering levothyroxine at an initial dose of 1 – 2 g/weight/day. This case report aims to show that AIT can show a wide range of symptoms and effects from the treatment that given to patient.